PEMANFAATAN TUMBUHAN MANGROVE OLEH MASYARAKAT DESA BAKAU BESAR LAUT KECAMATAN SUNGAI PINYUH KABUPATEN MEMPAWAH - Rosyada, Alfa; Anwari, M Sofwan; Muflihati, . (JURNAL HUTAN LESTARI, 2018)
Mangrove forests have a very important role in coastal areas. One of the knowledge about the utilization of mangrove plants is located in Bakau Besar Laut Village Sungai Pinyuh District Mempawah Regency. The purpose of this study was to find the kinds of mangrove, benefits and ways of utilizing mangrove plants that was used by the society in Bakau Besar Laut Village. Methods of data collection were done through interviews and question naires to determine the respondents using snowball sampling technique. Data recorded from plants was the local name, latin name, family name part of the plant used, and how to use them. Plants that used by the society were about 23 species from 18 families, and divided into six groups of uses, namely medicine plants (13 species), firewood (7 species), food (5 species), aromatics (4 species), wicker craft materials (3 species), andÂ  dyes (2 species).Keywords: Bakau besar laut village, Mangrove, snowball Sampling,Â the utilization of mangrove plants.